Multicenter Early Radiographic Outcomes of Triplanar Tarsometatarsal Arthrodesis With Early Weightbearing. (August 2019) - Ray, Justin J.; Koay, Jennifer; Dayton, Paul D.; Hatch, Daniel J.; Smith, Bret; Santrock, Robert D.
Background: Hallux valgus is a multiplanar deformity of the first ray. Traditional correction methods prioritize the transverse plane, a potential factor resulting in high recurrence rates. Triplanar first tarsometatarsal (TMT) arthrodesis uses a multiplanar approach to correct hallux valgus in all 3 anatomical planes at the apex of the deformity. The purpose of this study was to investigate early radiographic outcomes and complications of triplanar first TMT arthrodesis with early weightbearing. Methods: Radiographs and charts were retrospectively reviewed for 57 patients (62 feet) aged 39.7 ± 18.9 years undergoing triplanar first TMT arthrodesis at 4 institutions between 2015 and 2017. Patients were allowed early full weightbearing in a boot walker. Postoperative radiographs were compared with preoperative radiographs for hallux valgus angle (HVA), intermetatarsal angle (IMA), tibial sesamoid position (TSP), and lateral round sign. Any complications were recorded. Results: Radiographic results demonstrated significant improvements in IMA (13.6 ± 2.7 degrees to 6.6 ± 1.9 degrees), HVA (24.2 ± 9.3 degrees to 9.7 ± 5.1 degrees), and TSP (5.0 ± 1.3 to 1.9 ± 0.9) from preoperative to final follow-up ( P < .001). Lateral round sign was present in 2 of 62 feet (3.2%) at final follow-up compared with 52 of 62 feet (83.9%) preoperatively. At final follow-up, recurrence was 3.2% (2/62 feet), and the symptomatic nonunion rate was 1.6% (1/62 feet). Two patients required hardware removal, and 2 patients required additional Akin osteotomy. Conclusion: Early radiographic outcomes of triplanar first TMT arthrodesis with early weightbearing were promising with low recurrence rates and maintenance of correction. Level of Evidence: Level IV, retrospective case series.